Optimalisasi Kualitas Kenyamanan Thermal di Ruang Kantor dan Aula Islamic Centre UIN SUSKA Riau - Nurlaili Nurlaili; Novirza Novirza (Lembaga penelitian dan pengabdian kepada Masyarakat, 2013)
Energy conservation in buildings is a serious attention in Indonesia, including as one of the focus in the Roadmap Research, Development, and Application of Science and Technology Field of New and Renewable Energy Sources from the Ministry of Research and Technology. This study aims to determine the thermal calculator PMV” provided by Luma Sense Technologies to get the value of PMV-PPD and thermal comfort employee feels comfortable with the PMV value of 0.7 (slightly warm) and PPD value of 16.89 (mean 16.89% of people feel uncomfortable in the room), but when the air conditioner off at 12.00 am, the PMV value rose to 2.76 (Hot) and PPD 96.57 (mean 96.57% of people feel uncomfortable). As for the condition of the hall with AC On the value of PMV = 1.8 (warm), PPD value of 67.89 (mean 67.89% of people feel uncomfortable), and so the AC off at 12.00 pm, the PMV value rose to 3.1 (Hot) with PPD 99, 5 (mean everyone does not feel of State Islamic University of Suska Riau at Islamic center relies heavily on the use of air conditioning, so the AC Off the thermal comfort is reduced drastically, especially in the middle of the day and hot weather during the term of the study. Based on the analysis and discussion of design concepts found most appropriate to the condition of the building with the addition of the IC is the insulation of the building, with one of the alternative types of polyurethane foam insulation is spray applied a simple and practical and appropriate for buildings that have been standing.